Tourism's Economic Impact in West Southeast Nusa: Input-Output Analysis Approach - Achmad Fioren Jati Golo; Eris Girasto; Rummana Labista Syahla Dewi; Salma Nabila Asrizal (Jurnal Ekonomi, 2024)
West Southeast Nusa has great tourism potential that should be developed to boost the macro economy which leads to increased community welfare. This study uses IO analysis to see the multiplier effect and the total effect of the tourism sector’s impact on output, employment, and income. The results show that the tourism sector is one of the key sectors in the economy of West Southeast Nusa Province, significantly increasing output, employment, and income. The large contribution of the tourism sector to the West Southeast Nusa economy should be a special concern for the government. Digitalization and investment in tourism sector and human resources must be increased to unleash the full potential of this sector and significantly boost the economy in West Southeast Nusa Province.